2012
DOI: 10.1534/genetics.112.144246
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Trait Genomic Selection Methods Increase Genetic Value Prediction Accuracy

Abstract: Genetic correlations between quantitative traits measured in many breeding programs are pervasive. These correlations indicate that measurements of one trait carry information on other traits. Current single-trait (univariate) genomic selection does not take advantage of this information. Multivariate genomic selection on multiple traits could accomplish this but has been little explored and tested in practical breeding programs. In this study, three multivariate linear models (i.e., GBLUP, BayesA, and BayesCp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
518
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(565 citation statements)
references
References 16 publications
40
518
4
3
Order By: Relevance
“…Using such a predictor trait may result in an improvement of the trait of interest at a low cost. Also in genomic selection, an additional gain in accuracy can be achieved using predictor traits, as it was shown using both deterministic (Calus et al, 2013) and empirical simulations Jia and Jannink, 2012). Both empirical studies had predictor traits measured on both the reference animals and evaluated animals.…”
Section: Introductionmentioning
confidence: 99%
“…Using such a predictor trait may result in an improvement of the trait of interest at a low cost. Also in genomic selection, an additional gain in accuracy can be achieved using predictor traits, as it was shown using both deterministic (Calus et al, 2013) and empirical simulations Jia and Jannink, 2012). Both empirical studies had predictor traits measured on both the reference animals and evaluated animals.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Yang et al (2010) suggested using whole-genome regressions (WGRs) (Meuwissen et al 2001) to assess the proportion of variance of a trait or disease risk that can be explained by a regression of phenotypes on common SNPs or genomic heritability and a related parameter, the "missing heritability." More recently, WGR models have been extended for the analysis of systems of multiple traits, so the concept of genomic correlation also has entered into the picture (Jia and Jannink 2012;Lee et al 2012). For instance, Maier et al (2015) used multivariate WGR models and reported estimates of genetic correlations between psychiatric disorders, and Furlotte and Eskin (2015) presented a methodology that incorporates genetic marker information for the analysis of multiple traits that, according to the authors, "provide fundamental insights into the nature of co-expressed genes."…”
mentioning
confidence: 99%
“…By evaluating power performance, it is shown that it can be advantageous to perform the proposed pleiotropy analysis instead of individual trait analysis. [1][2][3][4][5][6][7][8][9][10]27,44 Among other merits, the MFLM can handle missing genotype data naturally.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] To our knowledge, metaanalysis and pleiotropy analysis have been performed separately so far, and there are no gene-based meta-analysis methods for combining multiple studies together and for carrying out a unified pleiotropy analysis. Here, multivariate functional linear models (MFLM) are developed to connect genetic variant data to multiple quantitative traits adjusting for covariates in a meta-analysis context.…”
Section: Introductionmentioning
confidence: 99%